Low-income women and the construction of ways of participation in written culture (Minas Gerais, Brazil, 20th Century) - Ana Maria de Oliveira Galvão; Kelly Aparecida De Sousa Queiroz; Mônica Yumi Jinzenji (Arizona State University, 2013)
How do low-income women build, throughout their lives, ways to participate in written culture? What are the main instances that "sponsor" this participation? What kind of participation is built? This article aims to analyze the tactics through which low-income, uneducated black women, who were born in rural areas and today live in a slum in Belo Horizonte, Minas Gerais, Brazil, built their participation in written culture during the mid-20th century. Oral history was used as methodological approach to interview 33 women. A survey of secondary data about their hometowns was also performed. The theoretical framework includes the works done in the fields of cultural history, sociology of reading, and orality and literacy. The results of the research show that family, school, the urban environment, and the participation in social movements were, in general, responsible for the women's participation in written culture. The research also shows that they performed different ways of participation. Some women became literary readers, wrote poems and music, and developed very organized speeches. However, most of them experienced a distant relationship with the written world: they learned how to sign their names and developed tactics to live in a written-centered society, such as memorization and the help from people who know how to read and write.